Pengaruh Latihan Small Sided Games dan Audio-Visual terhadap Hasil Passing Sepak Bola Siswa Ekstrakurikuler SDN 2 Petaling - Arba Septiawan; Bayu Iswana; Bambang Hermansah (EduInovasi: Journal of Basic Educational Studies, 2026)
This study aimed to determine the effect of Small-Sided Games (SSG) and audio-visual training on the soccer passing skills of extracurricular students at SDN 2 Petaling, and to compare the effectiveness of both methods. The research method was a true experimental design with a two-group pre-test post-test design. The sample consisted of 20 students selected via total sampling, divided into Group A (SSG training) and Group B (audio-visual training) using ordinal pairing. Data were collected using a 40-second soccer short passing test. The treatment program was administered over 16 sessions. Data were analyzed using paired and independent sample t-tests via SPSS 26. The results showed that both methods significantly improved students' passing performance (Sig. 0.000 < 0.05). However, the SSG training group showed a higher average improvement of 19.40 points (from 17.40 to 36.80) compared to the audio-visual group, which improved by 11.90 points (from 18.10 to 30.00). In conclusion, the Small-Sided Games training method is proven to be more effective in improving soccer passing skills for extracurricular students at SDN 2 Petaling.